Adapting to crisis and unveiling the digital shift: a systematic literature review of digital competence in education related to COVID-19 - Zhao, Yu; Sánchez-Gómez, María Cruz; Pinto-Llorente, Ana María; Sánchez Prieto, Raúl (Frontiers in Education, 2025)
Nowadays, with technology penetrating into every aspect of our life, the ways to acquire knowledge has been greatly revolutionized. The outbreak of the Coronavirus (COVID-19) has accelerated digital informatization in education and the educational model has been transformed substantially. The demand for digital competence is at record high. The purpose of this study is to systematically explore digital competence in different national educational contexts during the COVID-19 pandemic (2019–2021), to provide academics with the current state of digital competence in education and main research trends in digital competence in education during this period, elucidate the impact of pandemic on digital competence, and explore the limitations in the implementation of digital competence in educational research. The results indicate that most research on digital competence in educational contexts related to COVID-19 focused on the current state of the digital competence of teachers and students, especially those in higher education and formal learning context. Still, with the situation compounded, the researchers furthered their study by investigating the factors that influenced digital competence in order to address educational challenges in a pandemic context. In addition, teachers and students were still not well equipped as for digital competence though their digital awareness and digital readiness in the teaching and learning process increased. It is recommended to promote and enhance digital competence training in order to improve students’ achievement and the quality of education.